Opinions of Students at Turkish and German Universities on Turkey in the EU Accession Process - (:unkn) unknown (EDAM, 2009)
Turkey's candidacy for accession to the European Union (EU) dates back to many years and is still a current and highly disputed issue. This study was conducted to determine the opinions of students at Turkish and German universities on Turkey in relation to the European Union. Two hundred twenty six German students participated in the study from the departments of Turkish Translation and Interpretation and Asian Languages at the University of Bonn, Germany, and 270 Turkish students participated in the study from Ataturk Faculty of Education in Marmara University, Istanbul-Turkey. The research data were collected through a questionnaire created by Dartan, Nas, Akman, and Savran (2004). The questionnaire was prepared in both Turkish and German languages and consisted of 27 items. Five items of the questionnaire aimed at the collection of personal data and 17 items are responded with yes, no, uncertain, no idea. These items were categorized under four dimensions consisting of Turkey's general structure, Turkey's economic and political situation, Turkey's foreign policy, and general opinions on Turkey's accession to the EU. The other 5 items consisted of multiple or one choice questions, which investigated students' approach to the EU from different perspectives. According to the findings, responses given by two groups of students have been interpreted comparatively. According to the results of the study, Turkish students specified health issues, economic and political instabilities, and debates over secularism as the fundamental problems in accession of Turkey to the EU. Turkish students believe that Turkey's accession to the EU is a very long process and perhaps a process that would never end. German students had a more positive approach to Turkey's accession to the EU. However, students in Germany highlighted religion, population, and economic factors as the most important obstacles to the accession of Turkey to the EU. Furthermore, contrary to Turkish students, students in Germany believe that Turkey is ready to join the EU. Both groups confirm that Turkey is a secular and democratic country and that it provides a model for the other Islamic countries.
Keywords: European Union; Education; Democracy; Political Situation